A Study on the Effect of Television in Comprehension of Organic Farming Technology (Indian Journal of Extension Education, 2014)
The present study was conducted to determine the effect of television in comprehension of organic farming technology by farmers of Jabalpur District. The study was undertaken with 100 farmers in 2 villages selecting 50 farmers from each village in Panagar block of Jabalpur District, It was recorded that majority of the respondents who viewed television belonged to middle age group while the maximum non viewers were in category of young age group. The perusal of finding of the study indicated that respondents were educated up to middle and above level and belonged to OBC caste living in joint family system. In the present study maximum viewers belonged to middle category of economic motivation, having cosmopoliteness and extension participation .Majority of the viewers showed preference to view organic farming technology of crop production . The comparative analysis indicated that there had been an appreciable change in the knowledge and comprehension of the viewers than non-viewers when technology was exposed through television.